Association between park vitality and commercial vitality: a case study in Chengdu - Lu Che; Yuan Deng; Sidai Guo (Journal of Asian Architecture and Building Engineering, 2025)
Urban vitality stands as a pivotal metric for evaluating the sustainability and appeal of urban environments. Global experiences underscore the significance of parks and shopping centers as crucial components of urban vitality spaces. However, existing literature predominantly concentrates on the individual impacts of parks or shopping centers on urban vitality, with limited exploration into the vitality relationship between them, often relying on linear correlation analyses. To address this gap, this study, centered on the renowned Park City of Chengdu in China, employs Baidu heatmap and POI data, utilizing a combination of spatial syntax and linear and non-linear analysis methods to examine the influence of road accessibility on the vitality of shopping malls and parks, as well as their correlation. Findings indicate: (1) High-vitality shopping malls primarily cluster within the first ring road, while park utilization is notably higher in the southern urban area. (2) High-vitality parks and shopping centers are situated in regions characterized by elevated global integration and efficiency values, suggesting their vitality is influenced by road accessibility. (3) Linear correlation analysis, with global integration and efficiency values controlled, yields correlation coefficients of 0.797 and 0.795 for high-vitality parks and shopping centers, respectively. Non-linear correlation analysis indicates a correlation coefficient close to 0.7 between park vitality and shopping mall vitality, highlighting a strong correlation between them. This study elucidates the critical relationship between park vitality and commercial vitality in urban layout, offering valuable insights for urban planning strategies aimed at promoting sustainable urban development.